Lecturers’ Perception of the Use of Social Media for English Language Teaching - Tiffani Widya Larasati; Yuri Lolita (Program Studi Bahasa Inggris Universitas Trunojoyo Madura, 2023)
The purpose of this study was to see how English lecturers’ perceptions of the use of social media for English Language teaching. This study is limited to 4 aspects (Activities, Motivation, Enhancing students’ skills, and effectiveness). This research was conducted at the English Department at a university in Surabaya using social media for teaching English by lecturers. This study using a case study design and semi-structured interview, by organizing, interpreting, and representing the data. A total of 8 lecturers have participated to be interviewed to know about their perception on the use of social media for English Language Teaching. The results showed that the social media most primarily used by the English lecturers are WhatsApp and Email. The result of the interviews showed about the four aspects that had been determined. They are; 1). Activities when using social media in teaching English; discussion, communication, sharing subjects’ materials, collecting an assignment, giving assignments. 2). The use of Social media can increase students and lecturers’ motivation; improving learning motivation, active, creative, increasing self-confidence, and interesting. 3). The use of social media can enhance students’ English skills; enhancing speaking skill, writing skill, pronunciation, vocabulary. 4). The effectiveness of social media use in teaching English; easy to access, easy to understand, easy to use, easy to be practiced.